M.N. Roy: A Study of revolution and reason in Indian Politics. - Grover, D. C. (Calcutta, 1973)
This work the revised version of Kurukshetra University doctoral thesis on M. N. Roy's Political Philosophy is an attempt in the study of revolution and reason in Indian politics. From communism to humanism is a fascinating study of M. N. Roy, in whom the revolutionary process joins hand with rational process. The parallel march of revolution and reason in the evolution of Roy's political ideas, helped him to develop a scientific philosophy of Indian politics.
Keywords: Political Science .